High‐Performance Photovoltaic Detector Based on MoTe2/MoS2 Van der Waals Heterostructure. Issue 9 (22nd January 2018) - Chen, Yan; Wang, Xudong; Wu, Guangjian; Wang, Zhen; Fang, Hehai; Lin, Tie; Sun, Shuo; Shen, Hong; Hu, Weida; Wang, Jianlu; Sun, Jinglan; Meng, Xiangjian; et al.
Abstract: Van der Waals heterostructures based on 2D layered materials have received wide attention for their multiple applications in optoelectronic devices, such as solar cells, light‐emitting devices, and photodiodes. In this work, high‐performance photovoltaic photodetectors based on MoTe2 /MoS2 vertical heterojunctions are demonstrated by exfoliating‐restacking approach. The fundamental electric properties and band structures of the junction are revealed and analyzed. It is shown that this kind of photodetectors can operate under zero bias with high on/off ratio (>10 5 ) and ultralow dark current (≈3 pA). Moreover, a fast response time of 60 µs and high photoresponsivity of 46 mA W −1 are also attained at room temperature. The junctions based on 2D materials are expected to constitute the ultimate functional elements of nanoscale electronic and optoelectronic applications. Abstract : High‐performance photovoltaic photodetectors based on MoTe2 /MoS2 heterojunction are demonstrated. The photoresponse under different biases is measured and the corresponding light‐induced charge transport is discussed. As a self‐powered photodetector, the vertical 2D p–n junctions achieve fast response and broad detection wavelength range. These outstanding properties indicate that 2D van der Waals junctions possess promising applications in photodetection, on‐chip logic circuits, and related applications.